Maximizers and Satisficers in Consumer Culture Changes - Roubal, Ondřej (Communication Today, 2018)
Consumer culture in the era of late modernity undergoes dynamic changes of global significance. One of the key attributes of these changes constitutes an increasing supply of opportunities and quantitative volumes of different product options. However, this trait of so-called “consumer society” is largely ambivalent. On the one hand, expansion of opportunities constitutes a desirable source of realisation and emancipation of personal freedoms and independence; on the other hand, demands on the ability to individually manage the consequences of one’s own decisions (and to take responsibility for these decisions) increase. We can see this ambivalence well with respect to an example of two different adaptive strategies of consumer choice – maximizers and satisficers. Maximizers are likely to achieve better objective outcomes of their selections than satisficers, but their subjective perception of these results is, according to empirical evidence, more affected by negative emotions. These and other findings should be used more extensively in the marketing practice associated with business strategies.